Klasifikasi Rendaku Dalam Buku Basic Kanji Volume I dan Volume II - Menik Diah Wardani; Idah Hamidah; Hartati Hartati (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2020)
The title of this research is Rendaku Classification in Basic Kanji Books Volume I and Volume II. Rendaku is the change of the non-voice consonants into a voiced consonant. The purpose of this research is to classifying the consonant changes of rendaku in Japanese language. This research is a qualitative descriptive study with data collection technique using the literature study tecniques. The method of analysis in this research is the determinants element technique. There are 38 data in the form of wago containing rendaku changes. Data source taken from Basic Kanji Volume 1 and Volume 2. The results of the analysis in this research found the changes in k→g as many as 10 data, changes in h→b as many as 7 data, changes in s/ts→z as many as 4 data, changes in t→d as many as 4 data. Based on the results of the analysis can be conclude that: 1) rendaku will appears on compound words, 2) rendaku will appear if in the second morpheme there are no other voiced consonant. Rendaku happened to morphemes kawa, kami, kata, kaki, ki, kaeri, kuchi, kuni, kusuri, kuruma, ha, hatake, harai, hiki, hito, hi, hosoi, sakana, sama, tsukuri, tsuyoi, tome, toshi, tomo, tera.